Fluid and Tissue Biomarkers of Lewy Body Dementia: Report of an LBDA Symposium - Scott, Gregory D.; Arnold, Moriah R.; Beach, Thomas G.; Gibbons, Christopher H.; Kanthasamy, Anumantha G.; Lebovitz, Russell M.; Lemstra, Afina W.; Shaw, Leslie M.; Teunissen, Charlotte E.; Zetterberg, Henrik; Taylor, Angela S.; Graham, Todd C.; et al. (Frontiers in Neurology, 2022)
The Lewy Body Dementia Association (LBDA) held a virtual event, the LBDA Biofluid/Tissue Biomarker Symposium, on January 25, 2021, to present advances in biomarkers for Lewy Body Dementia (LBD), which includes Dementia with Lewy Bodies (DLB) and Parkinson's Disease Dementia (PDD). The meeting featured eight internationally known scientists from Europe and the United States and attracted over 200 scientists and physicians from academic centers, the National Institutes of Health and the pharmaceutical industry. Methods for confirming and quantifying the presence of Lewy body and Alzheimer pathology as well as novel biomarkers were discussed.